2006
DOI: 10.1017/s095457940606055x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and circadian rhythms in children and adolescents with bipolar disorder

Abstract: The aim of this paper is to highlight the importance of the sleep-wake cycle in children and adolescents with bipolar disorder. After presenting an overview of the measurement and function of human sleep, we describe changes in sleep and circadian functioning across the life cycle. We then review evidence that, in adults, sleep and/or circadian rhythms are of considerable influence in the multifactorial causal chain implicated in relapse in bipolar disorder, discussing relevant mechanisms. The latter include a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 119 publications
2
51
0
Order By: Relevance
“…The patient did not meet criteria for insomnia but met criteria for delayed-phase syndrome. This finding is consistent with literature suggesting that sleep disturbance is a core symptom of patients with bipolar disorder [7,14,38,39] and evidence associating sleep deprivation with the onset of mania [40]. The patient also exhibited some dysfunctional beliefs about sleep measured on the DBAS [26] and SDQ [27].…”
Section: Discussionsupporting
confidence: 90%
“…The patient did not meet criteria for insomnia but met criteria for delayed-phase syndrome. This finding is consistent with literature suggesting that sleep disturbance is a core symptom of patients with bipolar disorder [7,14,38,39] and evidence associating sleep deprivation with the onset of mania [40]. The patient also exhibited some dysfunctional beliefs about sleep measured on the DBAS [26] and SDQ [27].…”
Section: Discussionsupporting
confidence: 90%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][80][81][82] However, molecular evidence for altered circadian clock in bipolar disorder is still lacking. It has been reported that similar components of the clock machinery underlie rhythmic gene expression in cultured fibroblasts as in the central clock in the SCN.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Changes in rest:activity and sleep:wake cycles are among the most prominent aspects of bipolar illness during both the manic and depressed phase (see references [5][6][7] for reviews). In bipolar patients, alterations in phase, period and amplitude of circadian rhythms have been documented by measuring core temperature, hormonal secretion or actigraphy.…”
Section: Introductionmentioning
confidence: 99%
“…23 A variety of sleep disturbances have been associated with symptoms of mood disorders among youth. 152,173,174 One study showed that depressed adolescent boys had short REM (rapid eye movement) latency and more frequent nighttime arousals, although depressed adolescent girls showed the same sleep patterns as their healthy counterparts. 175 Circadian phase shifts can occur before the onset of and during a depressive episode in adults and adolescents.…”
Section: Sleep Disturbancementioning
confidence: 99%